Literature Review: Self Regulated Learning dalam Pembelajaran Matematika - Vorry Navyola (J-PiMat : Jurnal Pendidikan Matematika, 2022)
Self Regulated Learning is a factor in the self that is owned by learners both teachers and students in order to achieve the goals of learning and teaching improvement. The abilities that can be obtained in learning mathematics include the ability to think creatively, the ability to think and act independently based on reasons that can be accounted for, and the ability to solve problems in a variety of situations. This article aimed at defining and explaning about Self Regulated Learning in mathematics. This is a literature based article taken from books, journal articles, and other documents related to the discussed topic. The results of his study found that, the development of Self Regulated Learning was needed by individuals in learning mathematics. Independent learning habits will be able to foster student independence in learning and students can also learn effectively and efficiently by referring to the expected goals.